Scale Construction of The Discipline Scale For Indonesian Air Force (TNI Angkatan Udara) Military Personnel (IMPI-D32) - Yashinta Levy Septiarly; Saifuddin Azwar (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2022)
This study aims to create a discipline measuring tool with good psychometric properties for Indonesian Air Force Military Personnel (IMPI-D32). It was conducted using an integration of self-discipline, motivation to obey, and discipline theories in a military context. The IMPI-D32 consists of 32 items and its construction are based on the Classical Theory Test. The item's content validity was estimated using the Aiken V index at a minimum of .690. Furthermore, the item discriminations showed that the corrected item-total correlation for all items is above .3. Meanwhile, the reliability estimation with the Spearman-Brown formula indicated a satisfactory coefficient value of .916. The standard error of measuring the IMPI-D32 was 3.439 with the confidence of true score interval between X-6 to X+6.